CSR in mission statements of Polish chemical industry companies (content analysis results) - Bortnowska Hanna; Seiler Bartosz (Management, 2022)
Due to the specific nature of their activities, chemical companies are exposed to significant reputational risk. One way to reduce this risk is by implementing a CSR policy. CSR can be built into the company’s strategy and communicated as a mission statement. The purpose of the article was to determine: 1. the types of values which chemical industry companies in Poland display in their mission statements, 2. if chemical industry companies in Poland display CSR values in their mission statements, 3. if these companies differ from others operating in the chemical sector in Poland in terms of displaying CSR in mission statements. The research was carried out through the Iramuteq program, which enabled content analysis of the collected research material. A total of 197 missions were analyzed to find that less than half of the examined chemical companies in Poland display CSR-related values sensu stricto in mission statements. It was also found that chemical companies (production-commercial) highlighted CSR values in their mission statements more often than analagous service-trade companies.